Cosmologias de campos escalares e simetrias de Noether - Bonato, Henrique de Oliveira (2024)
In this work, the theory of general relativity was used to study the inflationary period of the Universe and its later eras. Two models were proposed for this, the first, based on Canuto’s formalism, which allows a mapping between different cosmological eras through atomic and gravitational units, and the second, on the Brans-Dicke theory, which incorporates Mach’s principle. The field theory and Noether symmetries formalism were used. The first, to propose the sources of the gravitational field, present in the action of the models as a Klein-Gordon Lagrangian density. The second, in the generation of linearly dependent equations that condition the systems, and also producing an expression for the conserved charge, which helps in determining the variables. In the end, the analytical and numerical results obtained are used to verify whether they corroborate the period of inflation. Furthermore, the models are conducted to describe a post-inflationary period.